2016
DOI: 10.3389/fbioe.2016.00089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Novel Routes of Biomethane Utilization in a Life Cycle Perspective

Abstract: Biomethane, as a replacement for natural gas, reduces the use of fossil-based sources and supports the intended change from fossil to bio-based industry. The study assessed different biomethane utilization routes for production of methanol, dimethyl ether (DME), and ammonia, as fuel or platform chemicals and combined heat and power (CHP). Energy efficiency and environmental impacts of the different pathways was studied in a life cycle perspective covering the technical system from biomass production to the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Methane loss was found significantly varying with the different upgrading technologies (0.15% to 3% of the produced biogas) (Bailón and Hinge, 2012). A reduction of biomethane loss by 0.5% would reduce the GWP by 14-18% depending on the utilization route (Moghaddam et al, 2016).…”
Section: Extent Of Materials Processingmentioning
confidence: 99%
“…Methane loss was found significantly varying with the different upgrading technologies (0.15% to 3% of the produced biogas) (Bailón and Hinge, 2012). A reduction of biomethane loss by 0.5% would reduce the GWP by 14-18% depending on the utilization route (Moghaddam et al, 2016).…”
Section: Extent Of Materials Processingmentioning
confidence: 99%
“…However, ammonia based on biomethane may lead to lower environmental benefits compared to other utilisation pathways, e.g., methanol and DME production. 33 With regard to ammonia production from biomass, it was shown that the economic performance of biogas as the hydrogen source (via steam reforming) lies in between that of woody biomass gasification and electrolytic hydrogen from renewable sources. 34 Finally, ethylene, one of the most valuable petrochemicals, can also be produced from biomass through dehydration of bioethanol derived via fermentation.…”
Section: Reaction Chemistry and Engineering Perspectivementioning
confidence: 99%
“…This reduces the emissions of greenhouse gases and thus prevents climate change [23][24][25][26]. Furthermore, biomethane can be used as a platform chemical in various chemical and biochemical synthetic processes [28][29][30]. An example of biogas utilization is biomethanol production in the advanced biofuel plant BioMCN.…”
Section: Biogas Plants and Biogas Applicationsmentioning
confidence: 99%